A Mussel‐Inspired Persistent ROS‐Scavenging, Electroactive, and Osteoinductive Scaffold Based on Electrochemical‐Driven In Situ Nanoassembly. Issue 25 (20th May 2019) - Zhou, Ting; Yan, Liwei; Xie, Chaoming; Li, Pengfei; Jiang, Lili; Fang, Ju; Zhao, Cancan; Ren, Fuzeng; Wang, Kefeng; Wang, Yingbo; Zhang, Hongping; Guo, Tailin; et al.
Abstract: Conductive polymers are promising for bone regeneration because they can regulate cell behavior through electrical stimulation; moreover, they are antioxidative agents that can be used to protect cells and tissues from damage originating from reactive oxygen species (ROS). However, conductive polymers lack affinity to cells and osteoinductivity, which limits their application in tissue engineering. Herein, an electroactive, cell affinitive, persistent ROS‐scavenging, and osteoinductive porous Ti scaffold is prepared by the on‐surface in situ assembly of a polypyrrole‐polydopamine‐hydroxyapatite (PPy‐PDA‐HA) film through a layer‐by‐layer pulse electrodeposition (LBL‐PED) method. During LBL‐PED, the PPy‐PDA nanoparticles (NPs) and HA NPs are in situ synthesized and uniformly coated on a porous scaffold from inside to outside. PDA is entangled with and doped into PPy to enhance the ROS scavenging rate of the scaffold and realize repeatable, efficient ROS scavenging over a long period of time. HA and electrical stimulation synergistically promote osteogenic cell differentiation on PPy‐PDA‐HA films. Ultimately, the PPy‐PDA‐HA porous scaffold provides excellent bone regeneration through the synergistic effects of electroactivity, cell affinity, and antioxidative activity of the PPy‐PDA NPs and the osteoinductivity of HA NPs. This study provides a new strategy for functionalizing porous scaffolds that show great promise as implants for tissue regeneration. Abstract : An electroactive, antioxidative, cell affinitive, and osteoinductive polypyrrole‐polydopamine‐hydroxyapatite (PPy‐PDA‐HA) film is prepared on porous scaffolds through a layer‐by‐layer pulse electrodeposition (LBL‐PED) method. During LBL‐PED, the PPy‐PDA nanoparticles (NPs) and HA NPs are in situ‐synthesized and uniformly assembled on the scaffolds from inside to outside.